The Omahu Affair, the Law of Succession and the Native Land Court - Boast, Richard (Victoria University of Wellington Law Review, 2015)
This article discusses the Omahu affair, a prominent legal drama that took place in the late 19th century involving prominent Māori leaders from the Hawke’s Bay region. The case was the subject of numerous Native Land Court hearings, decisions of the ordinary courts, and ultimately a Privy Council decision in London. This article considers how tensions within the Māori community could drive cases in the Native Land Court, and explores the interconnections between that Court and the ordinary courts. It seeks to promote a more sophisticated view of the Court’s role, particularly in the context of inter-Māori disputes, as well as of the complexities of legal and political affairs in 19th century New Zealand. The article also raises some questions relating to the role of elites in the Māori community, and the interconnections between Māori and European elites in 19th century New Zealand.